Optimization of Human Interferon α2b Soluble Protein Overproduction and Primary Recovery of Its Inclusion Bodies - RATIH ASMANA NINGRUM; DEBBIE SOFIE RETNONINGRUM; YEYET CAHYATI; HENI RACHMAWATI (Microbiology Indonesia, 2011)
The hIFN2b open reading frame has been constructed and overexpressed in Escherichia coli BL21(DE3). The yields of protein purified using nickel column from inclusion bodies (IB) and total soluble proteins were 3.46 mg and 2.57 mg in 1 L culture, respectively. This research was aimed to obtain optimal condition for high level overproduction of soluble hIFNα2b as well as primary recovery of hIFN2b from IB. We used two different conditions for obtaining soluble protein, i.e. induction temperatures and inducer concentrations, and three different conditions for inclusion bodies, i.e. centrifugation speeds, washing and solubilizing buffers. Induction using 0.5 mM of isopropyl thiogalactopyranoside at 25 °C yielded 8.9 mg hIFN2b in 1 L culture. The best recovery of IB was achieved when 10 000 g was applied for centrifugation, 1% Triton X-100 in 50 mM Tris Cl pH 8.0 as washing buffer, and 8M guanidine HCl in 50 mM Tris Cl pH 8.0 containing 800 mM 2-mercaptoethanol as solubilizing buffer were used. At this optimal condition the yield of hIFN2b from IB was 28.85 mg in 1 L culture. The total recovery of hIFNα2b at optimal condition was 50% from IB and 14% from soluble protein. hIFN2b from IB was refolded by 9 d dialysis in refolding buffer (0.2 mM EDTA, 0.25 mM ditiothreitol, 50 mM Tris and 0.4 M urea pH 8.0).